The Influence of Nussa and Rara's Youtube Video Media on the Communication Skills of 4-5 Years Old Children - Munawaroh, Alisah Qodrunnada; Formen, Ali (Jurusan PGPAUD FIP UNNES, 2023)
The purpose of this study was determine the effect of the youtube nusa and rara on the communication sklls of children aged 4-5 years at RA NU MIFTAHUL FALAH Kudus. This research uses a quantitative approach, the type of experimental research with desain one group pretest posttest design. The population consist of 47 children aged 4-5 years in di RA NU Miftahul Falah Kudus. Sampling technique usng the type Non Probability Sampling with sampling jenuh metod. The total sample is 47 children. Data collection techniques using questionnaires and documentation. Data analysis techniques using inferential statistics with hypothesis testing using Paired Sample T-Test. Calsulation result with the help of the program SPSS, that is thitung 13.423 > ttabel 2.012 and value signifikan (2-tailed) 0,000, so that Ho is rejected and Ha is accepted. It means that there is a significant increase in children’s communication skill after being given treatment with animated nusa and rara. There is an average difference in children’s communication skills before and after being given treatment. This shows that the nusa and rara youtube are effectively used to increase children’s language vocabulary.